Analisis pengelolaan dana bantuan sosial desa covid-19 di Desa Ranggeh Kecamatan Gondang Wetan Kabupaten Pasuruan - Adiprakoso, Kenyndra Andryan; Yuliati, Anik (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study is itended to analyze descriptively how the entire process of managing social assistance finance in Ranggeh village, Gondang Wetan sub-district, Pasuruan district, starts from the budgeting process to the reporting stage, as well as measuring the accuracy of aid program realization using theory of effectiveness. The qualitative research methods is used in this research then analyzed descriptively. The data collection technique was carried out by interviewing the informants who had been determined by means of purposive sampling, field observations, research documentation and literature studies. Analysis of research data using data validation, data organization, presenting findings, and drawing hypotheses. The formulation of the hypothesis in this study continued to develop during the research with the initial assumption that the village government of Ranggeh managed the social assistance funds of Covid-19 in its village well and achieved its target. Furthermore, research shows that the village government has succeeded in implementing the village fund social assistance management program according to existing regulations and on target both in terms of theoretical effectiveness and meeting government goals and community needs in the field.